Studies of the faceting of epitaxial molybdenum oxide grown on Mo (110) - SHVETS, IGOR (My University, 2008)
We show that an oxide film can undergo a periodic self-faceting regime during growth. The oxide growth starts as a bulklike MoO2 surface oxide trilayer that wets the substrate in an orientation thermodynamically forbidden in the bulk. As this film continues to grow, it develops into a periodically faceted surface with nanowirelike structures composed of MoO2 (0 2 1) and (0 2 ?1) faces. Through the use of density functional theory, it is found that this faceted surface has a lower surface free energy than the initial growth orientation. Finally, using the theory of faceted surfaces, we demonstrate that the periodicity of the facets is likely an equilibrium state that is related to the elastic properties of the film.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; thin films